Fifteenth General Review of Quotas-Further Considerations. (Policy Papers; Policy Paper ;, 2021)
The paper revisits the two-pillar framework for assessing the adequacy of Fund resources. Responding to Directors suggestions, the quantitative pillar is updated to include alternative assumptions and to provide a longer-term perspective on likely resource needs. While quantitative estimates are generally somewhat lower after factoring in the alternative assumptions, these reductions are more than outweighed when the analysis is extended through the middle of the next decade, recognizing that the outcome of the 15th Review will likely determine permanent Fund resources through at least the middle of the next decade. The updated qualitative pillar analysis highlights reforms since the global financial crisis and discusses uncertainties in the global environment. It also provides an assessment of the general impact of the various qualitative considerations. Taken together, the two pillars continue to make a case for at least maintaining existing Fund resources. Against this background, the simulations in the paper cover three illustrative sizes for quota increases (50, 75, and 100 percent), centered on broadly maintaining Fund resources, assuming the New Arrangements to Borrow (NAB) is maintained at its current level and Bilateral Borrowing Agreements (BBAs) expire.